Guides to the eucharist in medieval Egypt (NEW YORK : FORDHAM UNIVERSITY PRESS, 2022)
"The fourteenth and fifteenth centuries witnessed a rising interest in Arabic texts describing and explaining the rituals of the Coptic Church of Egypt. This book provides readers with an English translation of excerpts from three key texts on the Coptic liturgy by Abū al-Barakāt ibn Kabar, Yūh.annā ibn Sabbā', and Pope Gabriel V. With a scholarly introduction to the works, their authors, and the Coptic liturgy, as well as a detailed explanatory apparatus, this volume provides a useful and needed introduction to the worship tradition of Egypt's Coptic Christians. Presented for the first time in English, these texts provide valuable points of comparison to other liturgical commentaries produced elsewhere in the medieval Christian world"--
The Lamp of Darkness / Abū al-Barakāt ibn Kabar -- The Precious Jewel / Yūḥannā ibn Sabbāʻ -- The Ritual Order / Gabriel V -- Appendix: Coptic Liturgical Chants.
JSTOR
Keywords: Lord's Supper -- Coptic Church; Lord's Supper (Liturgy); Eucharistie -- Église copte; Eucharistie -- Liturgie; Lord's Supper -- Coptic Church; Lord's Supper (Liturgy)